IN SILICO IDENTIFICATION OF APOBEC3B SMALL MOLECULE INHIBITORS FROM DTP-NCI LIBRARIES - MOHAMED, MARYAN MOHAMUD; JUSRIL, NOR ATIQAH; ADENAN, MOHD ILHAM; WEN, N. G. KWOK (International Journal of Applied Pharmaceutics, 2021)
Objective: APOBEC3B (A3B) enzyme causes C-to-T or C-to-G somatic alteration in the cancer genome, leading to the evolution of a broad spectrum of human cancers. The present study aims to identify A3B small molecule inhibitors using a top-down approach via pharmacoinformatic virtual screening. Methods: Virtual screening of 2951 drug-alike molecules with diversified structures from the National Cancer Institute Development Therapeutics Program (DTP-NCI) compounds library was performed using GOLD and AutoDock Vina docking programs against the 3D structure of A3B (PDB ID: 5TD5). Results: Amongst the docked compounds, Nordracorubin, NSC641233 and Raloxifene hydrochloride showed the most potent binding affinities towards A3B on both Autodock/Vina and GOLD. Several significant similarities were observed between A3B and the three hits, including hydrogen bonds and pi-pi stacking. The three compounds also exhibited interaction with the centralized zinc cofactor and amino acid residues that directly contribute the deaminase activity of A3B enzyme. Conclusion: We hypothesize that the findings from this study could significantly shorten the quest for novel molecules against the A3B after confirmation with subsequent in vitro and in vivo studies in the near future.